2013
DOI: 10.1177/0194599813500023
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Unplanned Hospital Readmission in Otolaryngology Patients

Abstract: Otolaryngology patients have unique risk factors that predict unplanned readmission within 30 days of discharge. These data identify specific patient characteristics and care processes that can be targeted with quality improvement interventions to decrease unplanned readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(144 citation statements)
references
References 29 publications
8
133
3
Order By: Relevance
“…Unplanned readmissions represent an interaction between patient factors, transitions of care, and postoperative complications. 24 In this study, most of the unplanned readmissions were related to surgical site infections, wound dehiscence, postoperative hemorrhage, and re-resection of positive margins. Surgical site infections have been targeted as a quality metric by the Surgical Care Improvement Project, which is endorsed by the Joint Commission and the National Quality Forum.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Unplanned readmissions represent an interaction between patient factors, transitions of care, and postoperative complications. 24 In this study, most of the unplanned readmissions were related to surgical site infections, wound dehiscence, postoperative hemorrhage, and re-resection of positive margins. Surgical site infections have been targeted as a quality metric by the Surgical Care Improvement Project, which is endorsed by the Joint Commission and the National Quality Forum.…”
Section: Discussionmentioning
confidence: 70%
“…We defined a 30-day unplanned readmission as an admission to any service in the hospital within 30 days of discharge that was not expected. 24 For thyroid surveillance, if a patient was dead within 12 months of completing radiation treatment, the metric was not evaluable. For surveillance imaging, if imaging was prompted by clinical suspicion of recurrence or the patient was dead within 6 months of the completion of therapy, the metric was not evaluable.…”
Section: Methodsmentioning
confidence: 99%
“…We defined a 30-day unplanned readmission as an admission to any service in the hospital within 30 days of discharge that was unexpected. 18 For thyroid function testing, if a patient was dead less than 12 months after completing radiotherapy, the metric was not evaluable. For surveillance imaging, if imaging was prompted by clinical suspicion of recurrence or the patient was dead less than 6 months after the completion of therapy, the metric was not evaluable.…”
Section: Methodsmentioning
confidence: 99%
“…25 Previous work examining risk factors for readmission of otolaryngology patients demonstrated that patients undergoing total laryngectomy (TL) are a high-risk population. 6 For the 1 year of otolaryngology discharges analyzed, the rate of 30-day unplanned readmission independent of complications following TL was 40%, more than a 5-fold increased risk of the 7.3% overall otolaryngology readmission rate. The details of the readmissions after TL were not elucidated in this prior study.…”
mentioning
confidence: 93%